MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA SMP MELALUI MODEL PEMBELAJARAN GROUP TO GROUP EXCHANGE - Devi Oktaviani (Academy of Education Journal, 2020)
This study aims to improve the learning outcomes of citizenship education materials on state defense efforts through the group to group exchange learning model. The subjects in this study were students of class IX Junior High Schol 32 OKU South Sumatera. This research is action research using quantitative data analysis by comparing test results in the first cycle and the second cycle. Learning outcomes in the first cycle showed an average value of 66 students with a percentage of completeness of 65%, while in the second cycle the average value of students was 72 with a 100% completeness percentage. The results showed that learning using the group to group exchange model can improve student learning outcomes.